Discriminador de frecuencia basado en resonadores “dual-mode” sintonizables - Moscoso Mártir, Álvaro; Molina-Fernández, Íñigo; Hong, Jiasheng (My University, 2013)
In this paper a novel varactor-tuned frequency discriminator that makes use of two tunable dual-mode microstrip resonators is demonstrated. In this circuit, the two tuned modes of the resonators are used independently to cover different frequency ranges, potentially doubling the tuning frequency range of the classic approach. To prove its validity a prototype of the tunable dual-mode microstrip resonator is manufactured and the measured results are used to study the frequency discriminator response. This new approach can cover almost an octave of frequency range from 1.05 to 2 GHz with a sensitivity of 45 V/GHz and 21 V/GHz for the first and second mode, respectively.
Presentado en el XXVIII Simposium Nacional de la Unin Cientfica Internacional de Radio. URSI 2013, Santiago de Compostela, 11 al 13 de septiembre de 2013.
Keywords: Radiofrecuencia